Simulation of Hybrid Induction Heating Distillation for Wateroil Mix in Refinery Pond Utilities - Talhah-Abdullah, Amir (2012)
The research project is mainly about the application of hybrid induction heating distillation for oil recovery process. . The objective of this study is to investigate the effectiveness of hybrid separation phenomenon by applying induction heating in distillation process. The scopes of this study are to study the reliability of Hybrid Induction Heating Distillation in water oil distillation, to study the amount of energy used for both typical and hybrid induction heating distillation and to study the effect ofntemperature to the heat change The induction heating concept will be applied into this research because of the characteristics of this concept will be improved the distillation processes. Induction heating is one of a method which providing fast, consistent heat for manufacturing applications which involved bonding or changing the properties of metals or other electrically conductive materials. Technically, induction process releases a quick heating because of the high power density installation. So, it offers the possibility to reach very high temperatures. The most important is, inducting heating can reduce the electrical energy consumption because of induction installations generally have a good efficiency. So then, there are two kinds of method will be carried out in this project, which are the induction heating technique and also the typical distillation technique. Then, the results of these kinds of methods will be comparing to determine the best results. Therefore, we expect that the high quality of the oil is recovered by using induction heating technique and also the temperature of the system can be controlled orderly by using this technique.